Isopropanol adsorption–oxidation over V2O5—A mass spectrometry study - Gambaro, Luis Alberto (2006)
The isopropanol adsorption–oxidation over V2O5 (transient study) was monitored by mass spectrometry (MS) of desorbed molecules produced over the catalyst by reactive interaction at 40, 100 and 150 °C. Then temperature programmed surface reaction (TPSR) tests were conducted to analyse the products again by MS. The acetone adsorption–oxidation was also studied at 40 °C by the same techniques. It was concluded that isopropanol molecules replace some of the water molecules adsorbed onto the V2O5 but do not interact with molecules of higher adsorption energies as methanol. The following products were identified by TPSR at low temperatures (<∼150 °C) variable amounts of water, isopropanol, propylene and acetone and, at ∼200–300 °C. water, CO, CO2, isopropyl ether. Isopropanol oxidation to acetone only use oxygen from V2O5. In turn, CO and CO2 desorptions are related with incomplete isopropanol oxidation to acetone, which is limited by the proportion of oxygen available in the solid. Formation of CO and CO2 occurs at the expense of atmospheric oxygen (He impurity). For such temperatures, V2O5 shows acid and minima redox properties.